An experimental investigation of the mechanical variables influence on soybean biodiesel production using the response surface methodology - Timóteo Vieira, Wedja; Gabriel, Rafaela; Raphaela Braga de Melo, Karla; Maria de Oliveira Ribeiro, Lívia; Inácio Soletti , João; Helena Vieira de Carvalho, Sandra (Revista Brasileira de Engenharia de Biossistemas, 2022)
Biodiesel is a fuel derived from renewable sources such as vegetable oils, animal fats, or residual oils. Although it is a potential source of energy, the efficiency of the production of this fuel depends on several factors, including variables associated with the stirring and mixing process of the reactions. The proper choice of these variables can avoid the formation of vortices, favor the flow direction and the homogeneity of the mixture, and, consequently, contribute to a higher yield of biodiesel. In this context, the present work investigated the effect of agitation and mixing on the production of soybean biodiesel from the analysis of parameters: impeller (blade - turbine), stirring speed (150 rpm – 300 rpm), and baffle (with-without). For this, a 2³ factorial experimental design was carried out for the methylic and ethylic routes. In the reactions, the oil: alcohol molar ratio, amount of catalyst, time, and temperature were fixed. Experimental results indicated higher yields for reactions via the methylic route (more than 93%). Through the statistical analysis, it was also verified that the presence of a baffle and the use of a turbine impeller were the variables of greater statistical significance for the methylic and ethylic routes, respectively. These results showed that the variables considered had a significant impact on the yield of the reactions, although the reaction conditions remained constant, which reinforces that only the control of stirring and mixing parameters can promote optimal yields of the reactions, reducing costs with reagents, operating time, or temperature control.